Prisons and Embodiment: Self-Management Strategies of an Incarcerated Population. (October 2019) - Choudhry, Khurshid; Armstrong, David; Dregan, Alexandru
Weight gain and obesity in prison are, like elsewhere, associated with an increase in caloric intake and reduction in physical activity, but these factors are not solely under the control of a prisoner. Nineteen semistructured interviews were conducted in two male prisons in the United Kingdom to explore participants' thoughts, beliefs, and feelings on the role prison plays on weight change. Data from interviews were analyzed through grounded theory methodology. The concept of embodiment was used to explain not only how prisoners tend to believe the physical and emotional consequences of imprisonment could adversely affect weight and health but also how they adapted behaviors toward their health to try to take back control and power over their lives. The changes in prisoners' health-related behavior due to imprisonment show similarities to those seen in individuals responding to chronic illnesses, which suggest that imprisonment might be viewed as akin to an illness of the body.